Development of recloser coordination programming for distributed generation islanding distribution network - Muangchareon, Sujarit; Ngaopitakkul, Atthapol (My University, 2013)
When faults occur during islanding, faults should be eliminated before the power system is unstable. An islanding system is normally a weak system. The setting of protective devices should be completed before going back to the normal operation. This paper focuses on the impact of protective device when distributed generation is considered in islanding condition, then resulting in protection of the electrical system malfunctions. To overcome this problem, the setting of recloser coordination is investigated in this paper. The fault current and protection coordination is considered for protective device. The results show that the setting recloser for islanding condition, when recloser is set using proposed technique, it can reduce complexity and increase security of recloser.
Keywords: Distributed generation; Distribution System; Islanding; Protective device; Recloser coordination